International law : our common future - Gibney, Mark (New York: London; Routledge, 2020)
"International Law: Our Common Future offers a dynamic approach to the study of international law that actively engages students in ways that more traditional textbooks do not. One way this is achieved is by focusing on recent events, including international terrorism, extraordinary rendition, the legality of drone strikes, environmental devastation, and human rights. Another is by having students wrestle with actual court rulings rather than being given short summaries of these decisions. These cases, which are from a wide array of international, regional, and domestic tribunals, are followed by a series of provocative and challenging questions and prompts that will naturally lead to classroom discussion and debate. The book recognizes the importance of visual media in terms of student learning. In addition to photographs of individuals and events that feature prominently in the development of international law, each chapter has sections entitled "International Law at the Movies" which highlight feature films and documentaries that explore the topic at hand. What students will quickly come to realize is that international law is not a distant and abstract entity, but rather, is intimately connected to various aspects of their daily lives. The book shows some of the remarkable changes in international law, most notably the declining importance of the role of the state. As a final point, the book is written in an engaging, almost conversational, style that is accessible to students in a wide array of academic disciplines"--
Fighting terrorism through law -- Detaining "enemy combatants" and suspected terrorists -- Extraordinary rendition -- Just ad bellum -- Jus in bello -- Individual accountability -- International crime -- Corporate accountability -- State responsibility and jurisdictional limitations -- Foreign and domestic immunities -- Poverty & disease -- Vulnerable populations -- Concluding thoughts.
Includes bibliographical references, filmography and index.
Keywords: International law; International law; Droit international